2001
DOI: 10.1016/s0304-3959(01)00336-0
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids attenuate capsaicin-evoked hyperalgesia through spinal and peripheral mechanisms

Abstract: Previous studies in our laboratory have demonstrated that cannabinoids administered intravenously attenuate the duration of nocifensive behavior and block the development of hyperalgesia produced by intraplantar injection of capsaicin. In the present study, we extended these observations and determined whether cannabinoids attenuate capsaicin-evoked pain and hyperalgesia through spinal and peripheral mechanisms, and whether the antihyperalgesia was receptor mediated. Separate groups of rats were pretreated 7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 56 publications
4
70
0
1
Order By: Relevance
“…Taken together with previous reports 9, [19][20][21][22]30,[42][43][44] , this study presents a strong basis for the design of novel synthetic cannabinoids that do not cross the blood-brain barrier as a new class of peripherally acting analgesics without the psychotropic liability of centrally acting CB 1 agonists.…”
Section: Discussionsupporting
confidence: 70%
“…Taken together with previous reports 9, [19][20][21][22]30,[42][43][44] , this study presents a strong basis for the design of novel synthetic cannabinoids that do not cross the blood-brain barrier as a new class of peripherally acting analgesics without the psychotropic liability of centrally acting CB 1 agonists.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the endocannabinoid anandamide inhibits capsaicin-evoked CGRP release from rat hind paw skin in vitro (Richardson et al, 1998), and the nonselective cannabinoid receptor agonist WIN 55,212-2, injected directly into the hind paw, inhibits mechanical allodynia and thermal hyperalgesia induced by capsaicin injection in vivo (Johanek et al, 2001). Similarly, utilizing the partial sciatic ligation model of neuropathic pain, Fox et al (2001) showed that intraplantar injection of WIN 55,212-2 decreased mechanical allodynia.…”
Section: Discussionmentioning
confidence: 97%
“…While peripheral effects of cannabinoid agonists on nociceptive responses have not been explored in sensory neurons of CB1 −/− mice, the data shown here, when considered in the context of cannabinoid effects on nociceptors that are sensitive to SR141716A, raise the possibility of a novel cannabinoidresponsive receptor with similar pharmacology to CB1 that is expressed by nociceptive primary sensory neurons. Interestingly, while some studies found that the peripheral antihyperalgesic effects of can-nabinoids were blocked by the CB1 selective antagonist SR141716A (Richardson et al, 1998), another found only partial (60%) inhibition (Johanek et al, 2001), consistent with a non-CB1 receptor mechanism for peripheral cannabinoid effects on nociception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,20] Cannabinoid's analgesic action in cancer pain is less clear. [2,10,19] In a murine bone sarcoma pain model, systemic cannabinoids act through CBr1. [15,21] However, the role of peripheral CBr1 and CBr2 receptors in soft tissue carcinoma pain is not known.…”
Section: Introductionmentioning
confidence: 99%